BABYGOEASY Enterprise / Ain Nabilah Mohammad Ibrahim ... [et al.] - Mohammad Ibrahim, Ain Nabilah; Badrulhisam, Basyirah; Saifuddin, Farah Hannani; Naim, Nur 'Ismah; Wan Mohd Rahimi, Wan Siti Nursabihah (2020)
BabyGoEasy Enterprise is based on a partnership which it is consists of 5 members who hold different important position in the company such as General Manager, Marketing Manager, Financial Manager, Operation Manager and Administrative Manager. The business capital has amounted to RM826566 where the total contribution of each member is RM90000. This business plan is prepared for the CIMB Group Holding Bhd. to get the loan around RM140000 for the guarantee of our working capital. Our location is located at Damansara Utama, Petaling Jaya, Selangor. This business is categorized as Small Medium Enterprise (SME) which provides heat- easy baby bottles for the customers. The main purpose of this business is to provide products and services that can give an easier life to parents that are having a baby. We are specialized in travel-friendly baby’s bottle and variety color of case-warmer that can attract a lot of customers. Our main activity is manufacturing, producing or packaging and selling the baby’s bottles. Moreover, the price that we offered is RM120 for each set that consists of a baby’s bottle and a case-warmer. Our target market is among the middle and high-income communities and focused on busy working parents with a traveling lifestyle. The populations of them around the store’s area are quite high because our business was located near shopping malls, residential area and schools. Because of this, it will create a great opportunity for people to pass by our store frequently to get the travel-friendly baby’ bottles. Our company used a social media platform to expand our product such as Facebook and Instagram. In conclusion, we hope BabyGoEasy Enterprise can be a well-known company throughout the nation and can gain a greater profit and services from time to time. Lastly, we also want to become a first-choice company that people choose to purchase baby’s essential products.